The effects of different types of organic compound on the growth performance and development of paddy (Oryza sativa) MR220 shoots and roots explants / Nur Yasmin Zaini Abdullah - Zaini Abdullah, Nur Yasmin (Faculty of Plantation and Agrotechnology, 2015)
A study on the effects of different organic compound on the growth performance and development of paddy MR220 shoots and roots explants. This study was conducted in UiTM Jasin Campus in order to investigate the effects of using three types of organic additives on the same level of concentration towards the three treatments responsive to the number of shoots and roots produced for six weeks in culture medium. In this study, seeds explants of paddy cultivar MR220 were cultured on MS medium that have been supplemented with different kinds of organic compound which are young coconut water, old coconut water and coconut milk at 200 g L-1. Each treatment was replicated five times and the numbers of shoots and roots that initiated from the explants were recorded and the mean of five replicates explants were calculated. From this study, young coconut water shows the medium was result the highest number of shoots and roots produced followed by the old coconut water medium and coconut milk medium. The numbers of shoots were significantly influence by coconut water concentration.